USM PhD STUDENT WINS YOUNG SCIENTIST AWARD AND BEST ORAL PRESENTER AWARD AT REGIONAL CONFERENCE - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, May 2016 - A Ph.D student from Universiti Sains Malaysia (USM), Heng King Sern, did the university proud when she won the Young Scientist Award and First place for Best Oral Presenter Award at the recent 3rd Regional Conference on Biosensors, Biodiagnostics, Biochips and Biotechnology (3rdRC4Bs).